The impact of diabetic peripheral neuropathy on spatiotemporal gait parameters in stroke survivors: A case-control study - Mustapa, Nurul Amirah; Justine, Maria; Mohd Mustafah, Nadia; Manaf, Haidzir (Universiti Kebangsaan Malaysia, 2021)
The deterioration of gait performance following stroke is related to the impairment of sensorimotor function on the paretic side. Improper gait performance in post-stroke with additional diabetic peripheral neuropathy (DPN) on paretic and non-paretic legs may create destabilizing effects, including serious injuries and falls. Therefore, this study aimed to investigate the effect of DPN on spatiotemporal gait parameters in stroke survivors and determine the correlation of movement functioning and functional balance post-stroke with gait parameters. Ten stroke survivors with DPN, 10 stroke survivors without DPN and 10 healthy controls participated in this case-control study. Movement functioning and functional balance were assessed before the actual testing. Spatiotemporal gait parameters were recorded using the Nexus Vicon motion analysis system. Kruskal-Wallis test was used to analyze the gait parameters and Spearman’s rank-order correlation coefficient was used to identify the correlation between variables. Results showed that stroke survivors with DPN had longer stride time (temporal gait parameter, p = 0.001), lower cadence (p = 0.001) and greater gait variability than those without DPN and the healthy controls. The gait parameters were significantly correlated with movement functioning and functional balance in stroke survivors with DPN (p < 0.05). These findings suggested that DPN possibly affected the gait parameters in stroke survivors. DPN could also play a role in movement functioning and functional balance in stroke survivors.